2015
DOI: 10.2343/geochemj.2.0378
|View full text |Cite
|
Sign up to set email alerts
|

Differential dissolution technique for the geochemical separation of the calcite and dolomite of dolomitic limestones

Abstract: Trace element geochemistry for dolomitic limestones was carried out by chemical separation of the constituent calcite and dolomite. A five-minute treatment for fine-grained dolomitic limestone with 0.5 M acetic acid differentially dissolves the calcite, but 82-90% of dolomite remained undissolved. The fraction of dissolved dolomite contributed 2-17% to the calcite fraction, depending on the calcite/dolomite ratios of the samples. The residue of the acetic acid treatment was treated with 0.5 M HCl and an almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…We observed a remarkable decrease in pH values when B. thuringiensis NL-11 was incubated with dolostones, suggesting that B. thuringiensis NL-11 produced organic acids to enhance carbonate mineral dissolution and ion release. In the present study, acetic acid was found to be an effective material for mineral dissolution, which is consistent with the findings of previous studies (Toyama & Terakado, 2015).…”
Section: Mineral-weathering Potential Of Strain Nl-11supporting
confidence: 93%
“…We observed a remarkable decrease in pH values when B. thuringiensis NL-11 was incubated with dolostones, suggesting that B. thuringiensis NL-11 produced organic acids to enhance carbonate mineral dissolution and ion release. In the present study, acetic acid was found to be an effective material for mineral dissolution, which is consistent with the findings of previous studies (Toyama & Terakado, 2015).…”
Section: Mineral-weathering Potential Of Strain Nl-11supporting
confidence: 93%
“…Hyphae interspersed and penetrated the rock surface via cracks and other weak positions, intruded into the interior, produced mechanical damage, loosened the rock structure, increased the contact area, and formed a hyphaemineral aggregate, making the granite surface rough. This result was previously noted by Lian (2014),Peng et al (2015), andToyama and Terakado (2015).…”
supporting
confidence: 88%
“…Our results show that the most important factor influencing the weathering of A. niger was pH (x2), followed by vaccination quantity (x4), temperature (x1), and the influence of generation cycle (x3). It is clear that acidolysis is one important way to promote the microbial weathering of minerals (Wu et al, 2018;Welch and Ullman, 1993;Toyama and Terakado, 2015), and comprises both inorganic and organic acids (Lian, 2008). Data show that given the same pH conditions, organic acids are more likely to accelerate the dissolution of minerals than their inorganic counterparts because the former can combine proton exchange with ligand complexes in weathering to form a complex enhancing rock dissolution (Štyriaková et al, 2012).…”
Section: The Relationship Between Environmental Factors and A Niger Granite Weatheringmentioning
confidence: 99%
“…Therefore, the main contribution types of carbonate minerals can be distinguished by the comparison of Mg 2+ and Ca 2+ . If the ratio of Mg 2+ /Ca 2+ > 0.50, the weathering process may be controlled by dolomite dissolution; otherwise, it is controlled by calcite dissolution . Most of the Mg 2+ /Ca 2+ values in the Nanming River are less than 0.50, and the highest value is 0.64, suggesting that the riverine solute is mainly controlled by the secondary calcite precipitation.…”
Section: Resultsmentioning
confidence: 99%